STUDY OF UNNATURAL DEATHS IN FEMALES A MEDICO LEGAL STUDY AT GOVERNMENT MEDICAL COLLEGE, LATUR, MAHARASHTRA (Journal of Forensic Medicine & Toxicology, 2015)
The present study was undertaken in the department of Forensic Medicine & Toxicology, Government College Hospital, Latur, Maharashatra. Aims and objectives to study the incidences of unnatural deaths in females in which cases medico legal autopsied was conducted. A total 392 cases of unnatural female deaths were studied out of 985 autopsy conducted during examination of decease a brought for postmortem examination during the study period, inquest papers, police documents and photographs. Stastical analysis of data was done and presented a results and observations in tabular forms. Majority of female deaths were in age group was 21 to 30 years (44.39%) followed by 31 to 40 (20.66%), in majority of female victims were from rural area (78.79%). Maximum number of deaths were accidental, (62.75%), followed by suicidal (30.6%) rest were homicidal deaths (6.64%). Burns (61.99%) appeared as first cause of death followed by poisoning (17.09%) and trauma (9.69%) while least of deaths were caused due to electrocution (1.53).
Keywords: Unnatural deaths; Burns; Poisoning; Hanging,; Strangulation